Bullies, fights, and guns : testing self-control theory with juveniles - Nofziger, Stacey (Criminal justice (LFB Scholarly Publishing LLC), 2001)
Most examinations of juvenile violence are limited in the behaviors studied and the theories used. To address these issues Nofziger applies a test of Gottfredson and Hirschi's (1990) General Theory of Crime to a range of violent and intimidating acts. She explores bullying, fighting, and weapon related behaviors and tests the effects of self-control and opportunity with survey data on 1200 juveniles. The analysis indicates that greater self-control decreases intimidation and violence and that greater opportunity increases the same behaviors. The study supports self-control theory and suggests that lessened self-control and increased opportunity encourage the behaviors under investigation.